Lady smoke - Sebastian, Laura (Delacorte Press, 2019)
"After fleeing Astrea and regaining her freedom, Theo searches for new allies to help her reclaim her throne, although that comes at a steep price. And with her enemies closer than she thinks, Theo's fight to win back Astrea may prove not only impossible, but deadly"--